DESIGN AND DEVELOPMENT OF CUSTOMER COMPLAINT SERVICE APPLICATION OF PDAM TIRTANADI BRANCH MEDAN DENAI BASED ON ANDROID - Gea, Eniur; Cut Try Utari; Taufik Ismail Simanjuntak (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to design an Android-based customer complaint service application for PDAM Tirtanadi Medan Denai Branch, enhancing customer service efficiency and responsiveness to complaints. Methods: A descriptive qualitative approach was employed, gathering data through direct observation, interviews with customers and administrators, and a literature review. The system development process followed stages including system requirements analysis, design, code generation, testing using black-box methods, and support for maintenance. Results: The resulting application enables rapid, accessible complaint submission for users, providing an effective alternative to traditional call center services and significantly reducing response times for issues such as water quality and meter failures. Novelty: This research contributes an innovative approach for water utility companies in Indonesia by incorporating mobile technology to facilitate 24-hour, location-independent access to complaint services, enhancing service transparency and community satisfaction.